Analysis of morphological and anthropometric variations of clivus using cone beam computed tomography in adults - Maryam Abdolmaleki; Roshanak Ghafari; Reza Pourkhalili (Babol University of Medical Sciences, 2021)
Introduction: Clivus forms the middle part of the skull base, and different anatomical and pathologies variations can be created in this structure. The aim of this study was to determine the morphological variations and anthropometric analysis of clivus in CBCT images. Material & Methods: In this descriptive analytical study, CBCT images of 130 men and women over the age of 18 were evaluated using On-Demand 3D software. The width, length as well as skull base and clivus angle were measured. Clivus was also examined for anatomical variations such as pneumatization, canalis basilaris medianus, basilar invagination, fossa navicular is magna. Data were analyzed through one-way ANOVA and T-test using SPSS 22 (α<0.05). Results: The mean length of clivus was significantly higher in men (45.72mm) than in women (41.56mm) (P<0.001). The mean skull base angle was significantly higher in males (118.39 degrees) than in females (113.4 degrees) (P<0.001).The mean width and angle of clivus had no significant difference between two genders, and none of the study variables was significantly different in various age groups. The mean skull base angle was significantly higher (120.06 degrees) in patients who had basilar invagination (BI) (P<0.001). In the study of variations, 3 (2.3%) cases of incomplete pneumatization, 7 (5.4%) cases canalis basilar medianus of which 6 (4.6%) cases had fossa navicularis magna with mean length of 7.07 mm and 19 cases of BI (14.6%) with mean length of 3.55 mm were observed. Conclusion: Familiarity of the maxillofacial radiologist with the anatomical variations of clivus, which were also rare, is important to differentiate from lesions. In anthropometric analysis, the length and angle of the skull base may be used to determine gender.